The first equation is y = -x - 4.
By substituting the value of y from the first equation into the second equation, we get:
3x + (-x - 4) = 8.
Simplifying the equation, we have:
2x - 4 = 8.
Adding 4 to both sides of the equation, we have:
2x = 12.
Dividing both sides of the equation by 2, we get:
x = 6.
Therefore, the value of x is 6.
From the following system of equations, create a new equation by substituting the value of y from the first equation into the second equation.
From the new equation, evaluate the value of x.
y= - x - 4
3x +y = 8
Choose the correct option
(1 point)
1 answer